PENEGAKAN HUKUM TERHADAP CYBER CRIME DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK ATAS TINDAK PIDANA PENCEMARAN NAMA BAIK - Hutajulu, Maria Margaeta; Wahyuningsih, Sri Endah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Defamation in the digital realm is a form of cybercrime that has increasingly evolved alongside advancements in information technology. This act involves the dissemination of false or slanderous information that harms an individual's reputation. In the context of Indonesian law, defamation is regulated under Articles 310–321 of the Criminal Code (KUHP) and Law Number 1 of 2024, which amends the Electronic Information and Transactions Law (ITE Law), particularly Articles 27A and 27B paragraph (2) in conjunction with Article 45. The new national Criminal Code, effective January 2, 2026, also addresses defamation under Articles 433, 434, 435, 441, and 158. The evidentiary process for such crimes refers to Article 184 of the Criminal Procedure Code (KUHAP) and Article 5 of the ITE Law, which recognizes electronic information and documents, including their printouts, as valid legal evidence. In addition to repressive legal approaches, restorative justice as regulated in the National Police Chief’s Circular Letter SE/8/VII/2018 offers an alternative resolution to achieve substantive justice and legal certainty.Keywords: Law Enforcement, Cyber Crime, Defamation Crime.